Strategies to ensure success of microvascular free tissue transfer. - Gardiner, MD; Nanchahal, J (2010)
Free tissue transfer has revolutionised tissue reconstruction. Surgical technique is just one of many perioperative factors that determine the eventual outcome of the procedure. Many of these factors can be modified to ensure success. A search of the MEDLINE database using search terms related to perioperative management of free tissue transfer was performed. Further articles were identified by performing related-article searches in MEDLINE. The various perioperative factors that have been demonstrated to affect clinical outcome are discussed along with the current evidence for their optimisation. We present an algorithm for the management of patients undergoing free tissue transfer.